Analisis Kinerja Keuangan pada PT. Bank Perkreditan Rakyat (BPR) Kabupaten Simalungun - Eka Pratiwi Septania Parapat; Kisno Kisno; Benjamin Albert Simamora; Amelia Amelia (Politeknik Ganesha Medan, 2019)
The purpose of this study was to determine the financial condition based on liquidity ratio, solvency ratio, and profitability ratios in the PT. Bank Perkreditan Rakyat (BP R)KABUPATEN SIMALUNGUN Siantar in the years 2013 – 2015. Field research method by approaching directly to the company that became the object of study. Book study library to research conducted by several scientific books and papers relating to discussion conducted. The total assets in 2013 were Rp. 20.405.837.239 and increased in 2014 to Rp. 21.845.491.637, and in 2015 also increased to at Rp. 24.383.506.204. In 2013 the number of sales of Rp.3.527.453.681 the company makes a profit of Rp. 386.631.825. In 2014 sales increased to as much Rp. 3.820.802.620 with profit Rp. 440.536.679 and also increased from the previous year. In 2015 the company sales increased much Rp. 4.127.157.198, and makes a profit of Rp. 504.013.708